QUALITY OF LIFE, SELF-CARE ACTIVITIES, AND DIABETES CONTROL AMONG SCHOOL AGE CHILDREN - Abdella, Nabila Hassan Ali (International Journal of Research -GRANTHAALAYAH, 2017)
Self-care activities and control of blood sugar levels among children with type I diabetes have a positive impact on the quality of their lives. The aim of this study was to assess the quality of life, self-care activities, and diabetes control among school age children. A descriptive design was used in the conduction of this study. Setting: The study was carried out at the Health Insurance at El-Arab El-Shamla clinic at Port Said City. A random sample of 223 children was recruited from diabetes clinic. Tools of Data Collection, two tools were used to collect the necessary data to achieve the aim of the study in six months period. The study revealed that there were statistical positive correlation between children`s quality of life, diabetes control, and their self-care activities regarding diabetes. The study was concluded that there is a clear relationship between children’s high quality of life, control of diabetes and self-care activities. This study recommended that education and counseling for diabetic children are required to minimize the complications emergence and improve their quality of life.